Direct Electrodeposition of Zno Nanosheets Film on Plastic Substrate. Issue 1 (February 2020) - Xiao, Chuanhai; Sun, Shang; Lai, Qi
Abstract: A novel and simple method to directly assemble nanostructures onto plastic substrate via a quasi-2D electrodeposition approach was proposed. It was demonstrated that such synthetic method was feasible for flexible electronics, as exemplified by the fabrication of ZnO nanosheets film photoresponse devise onto flexible transparent, polyethylene terephthalate (PET) substrate that can withstand bending. This direct assembly strategy is general to other nanostructures onto plastic substrate which can be electrodeposited.